2015
DOI: 10.1063/1.4907801
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of oxide islands during the initial-stage oxidation of (100)Cu-Pt alloys

Abstract: Effect of gold composition on the orientations of oxide nuclei during the early stage oxidation of Cu-Au alloysThe initial-stage oxidation of (100) Cu-Pt alloys has been examined by in situ environmental transmission electron microscopy and ex situ atomic force microscopy (AFM). It is shown that the oxidation proceeds via the nucleation and growth of Cu 2 O islands that show dependence on the alloy composition and oxidation temperature. The kinetic measurements on the oxide nucleation reveal that both the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…prepared exactly in the same way but without the presence of the thiol SAM) did not evolve into islands. Hence, while the formation of oxide islands on bare metals, such as aluminium18 and copper–platinum alloy,19 was reported previously in the literature, the nature of the observed features is different here. This suggests that the alkanethiol molecules play an essential role in the formation of lamellar motifs.…”
Section: Resultssupporting
confidence: 40%
“…prepared exactly in the same way but without the presence of the thiol SAM) did not evolve into islands. Hence, while the formation of oxide islands on bare metals, such as aluminium18 and copper–platinum alloy,19 was reported previously in the literature, the nature of the observed features is different here. This suggests that the alkanethiol molecules play an essential role in the formation of lamellar motifs.…”
Section: Resultssupporting
confidence: 40%
“…The slow diffusion of Pt in the Cu-Au alloy not only affects the morphology such as distribution of the oxide island, but also reduces the rate of oxidation [142] . It is found that the nucleation kinetics and morphology can change as the function of oxidation temperature.…”
Section: Cu-pt Alloysmentioning
confidence: 99%
“…%Pt(100) alloy thin film at 800 ˚C and the SAED patterns shown in lower panel are obtained from regions 1, 2, and 3 marked in (a). Figure adapted from Ref[142]…”
mentioning
confidence: 99%
“…Luo et al [24] have performed a detailed in situ TEM investigation of the early oxidation stage on Cu-Au alloys and have determined that alloy composition had a significant effect on the nucleation barrier and the nucleation rate. Increasing the Au in the alloy shifted the nucleation mode from epitaxial to non-epitaxial, i.e., to a higher nucleation rate.…”
Section: The Role Of Two-phase Microstructure and The Sr Surface Actimentioning
confidence: 99%